Many Voices. Intertextualities as an Underlying Cultural Theory of ‘Escola do Porto’ - Gil, Bruno (Writingplace, 2018)
Several pedagogical experiences in architecture bring literary inputs to teaching, through a multidisciplinary curriculum with courses explicitly focusing on these relationships. Other pedagogical scenarios, even if admitting the relevance of literature references into design, have blended these semantic and structural translations implicitly in their teaching processes. The main goal of this article is to acknowledge the many voices of an implicit transfer between literature and architecture within a learning scenario at the Escola Superior de Belas-Artes do Porto (Fine Arts School in Porto) along with practice.Here, a process of modern acculturation was key, while aiming at modernity filtered by the local culture and tradition, and vice versa. One of its essential figures, Fernando Távora (1923-2005), recurrently quoted Fernando Pessoa while sharing his ideas with students. Reflecting on life and architecture, space and the world, Távora’s discourse was intuitively pedagogical. Fernando Távora embedded literature in his learning and teaching, while being highly engaged with everyday experience and practice. Távora integrated in his lifelong learning the writings of Fernando Pessoa, which among others implicitly contributed to the School of Porto. The article reflects on written essays of Fernando Távora and Alexandre Alves Costa and on architectural works by Álvaro Siza and Eduardo Souto de Moura. For the first, we will consider a specific period in the school, when architects had to complete written and designed pieces to become professors, while for the latter we will pick few architectural examples that illustrate the main argument of this paper.